PEWARISAN TARI GANDANG DI NAGARI PAUH IX KECAMATAN KURANJI KOTA PADANG - Indri Mayangsari; Indrayuda Indrayuda; Afifah Asriati (SENDRATASIK UNP, 2012)
This article aims to reveal and describe Inheritance Gandang Dance in Nagari Pauh District IX Kuranji Padang. This research is descriptive qualitative research method. Object of this study is on the Gandang Dance Pauh IX Kecamatan Kuranji Nagari Padang. Datas were collected through literature study, observation, interview and documentation. Data analysis was performed based on the ethnographic techniques. The findings of the research states that dance is a traditional dance Gandang in District IX Kuranji Pauh Nagari Padang, grow and flourish in the martial arts that exist in Nagari Pauh IX, precisely in the Katapiang area. In the development of dance Gandang had improvement in inheritance aspects. At the beginning of the growth of dance in Nagari Pauh Gandang IX, closed systems are more likely inheritance, through ties of blood and kinship. While the present when entering the 1975’s, has grown inheritance system tend to be closed that system through blood ties and kinship to open systems by learning from teacher to student in traditional self defence arts goals.